Hubungan Pengetahuan Perawat tentang Perawatan Terapi Intravena dengan Angka Kejadia Plebitis di Bangsal Bedah RSUD Prof. Dr. Margono Soekardjo Purwokerto - Handoyo,; Triyanto, Endang; Latifah, Lutfatul (Jurnal Keperawatan Soedirman, 2006)
Intravenous therapy is commonly used to treat patients and it is received through a peripheral cannula by most hospitalized patients. A consequence of intravenous (IV) devices is that risk of nosocomial infection is increased, particularly septicemia. Inflammation, hard vein and thrombophlebitis, and local tenderness are common complication of IV therapy. This can lead to enhanced morbidity and mortality rates. Appropriate training for nurses who perform intravenous cannulation, which include an understanding of techniques and the associated risks involved will enhance the safety of IV therapy. Planning and management of the therapy are necessary to minimize the risks presented. Lundgren and Ek, (1996) point out that the limited collective knowledge of nurses and the fact that nurses have their own routines. However, knowledge can be developed and made more accessible through reflection before, after, and while performing a task. The purpose of the study was to evaluate the relationship of nurses knowledge toward incidence of phlebitis for patients who admitted to surgical ward Margono Soekardjo Hospital of Purwokerto This study utilised survey. Of 30 nurses at surgical ward at Margono Soekardj Hospital are involved in this study. Respondents were chosen by quaote sampling method. Criteria of respondents were nurses at surgical ward who have graduated from DIII nursing with 1 year experience in clinical setting. Meanwhile, the criteria of patients were surgical patients who admitted to surgical ward with no complication and minimal three days hospitalised at surgical ward. Data were collected by using observation guideline of phlebitis. Data were analyzed using Kendal Tau test to see relationship of nurses knowledge level and the occurrence of phlebitis. The study show that there were no relationship of knowledge level toward the occurrence of phlebitis at surgical ward Margono Soekardjo Hospital of Purwokerto (Kendal Tau: - 0.086 levelof significance p: 0.617 CI : 95) .